(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Urinary tract infection (UTI) is common after pediatric kidney transplantation. The purpose of this study was to evaluate the prevalence of UTI and its risk factors in children and adolescents with kidney transplantation in Shiraz Transplant Center. Materials and Methods. All children with kidney transplantation from 1992 to 2008 who were under regular follow-up were included in this retrospective study. Confirmed episodes of UTI after the 1st month of kidney transplantation were reviewed. Results. Of the 216 patients younger than 19 years at the time of transplantation, 138 were included. The mean age at the time of kidney transplantation was 13.6 ± 3.5 years. Urinary tract infection was documented in 24 patients (15 girls and 9 boys), of whom 12 experienced 1 episode, 4 had 2 episodes, and 8 had more than 2 episodes, during a median follow-up period of 54 months. Of the patients with UTI, 14 (58%) had urinary reflux-obstruction disorders as the primary kidney disease, 6 (25%) had suffered hereditary diseases, 3 (12.5%) had glomerular disease, and 1 (4.5%) had a urinary calculus. Occurrence of UTI was not significantly different among children with different primary kidney disease (P = .22). Despite using prophylactic antibiotics after the 1st month of kidney transplantation in all 5 patients with neurogenic bladder, they all experienced recurrent UTI. Conclusions. Despite discontinuation of antibiotic therapy, UTI was uncommon in children after the first month of transplantation. Two significant risk factors for UTI were female gender and neurogenic bladder in this transplant population.